2009
DOI: 10.1016/j.cell.2008.10.051
|View full text |Cite
|
Sign up to set email alerts
|

FAM/USP9x, a Deubiquitinating Enzyme Essential for TGFβ Signaling, Controls Smad4 Monoubiquitination

Abstract: The assembly of the Smad complex is critical for TGFbeta signaling, yet the mechanisms that inactivate or empower nuclear Smad complexes are less understood. By means of siRNA screen we identified FAM (USP9x), a deubiquitinase acting as essential and evolutionarily conserved component in TGFbeta and bone morphogenetic protein signaling. Smad4 is monoubiquitinated in lysine 519 in vivo, a modification that inhibits Smad4 by impeding association with phospho-Smad2. FAM reverts this negative modification, re-empo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
443
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(470 citation statements)
references
References 36 publications
(52 reference statements)
14
443
1
Order By: Relevance
“…In recent years, more and more studies have revealed the involvement of deubiquitinating enzymes in cancers as well as in other diseases (8,48). USP9X, a ubiquitin-specific protease family member, is shown to regulate ubiquitination of different signal transduction pathway proteins, including AMPK (48), TGFb (8), ErbB2/HER2 (49), and ASK1 (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more studies have revealed the involvement of deubiquitinating enzymes in cancers as well as in other diseases (8,48). USP9X, a ubiquitin-specific protease family member, is shown to regulate ubiquitination of different signal transduction pathway proteins, including AMPK (48), TGFb (8), ErbB2/HER2 (49), and ASK1 (7).…”
Section: Discussionmentioning
confidence: 99%
“…5,6). USP9X has been shown to regulate multiple cellular functions (7)(8)(9)(10), and increased expression of USP9X in tumors is significantly associated with poor prognosis for patients with multiple myeloma (4). USP9X does not affect all apoptosis signaling pathways but specifically modulates those regulated by Mcl-1: USP9X binds to Mcl-1 and removes the Lys48-linked polyubiquitin chain that normally marks Mcl-1 for proteasomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…A third posttranslational modification that negatively regulates DNA binding is monoubiquitylation, which again induces disruption of DNA-bound SMAD complexes. Monoubiquitylation at Lys519 and, to a lesser extent, Lys507 in the MH2 domain of SMAD4 by the E3 ubiquitin ligase TIF1g (transcriptional intermediary factor 1g, also known as TRIM33 or ectodermin) disrupts the formation of SMAD2/3 -SMAD4 complexes and as a result their ability to bind DNA (Dupont et al 2009). This mechanism will be discussed in more detail below.…”
Section: Dna Binding Of Smad Complexes and Its Regulation By Posttranmentioning
confidence: 99%
“…So far, three DUBs have been reported to be involved in the regulation of this pathway: USP9X, AMSH-LP and UCHL5. USP9X positively regulates TGF-b signaling by deubiquitylating SMAD4 and promoting its association with SMAD2 (Dupont et al, 2009). USP9X also deubiquitylates the AMPK-related kinases NUAK1 and MARK4, implicated in the regulation of cell polarity and proliferation, and modulates their phosphorylation and activation by LKB1 (Al-Hakim et al, 2008).…”
Section: Signaling Pathwaysmentioning
confidence: 99%